THE EFFECT OF THE COMPREHENSIVE ELECTRONIC SYSTEM IN INCREASING THE STABILITY OF BANKING SYSTEM PERFORMANCE: AN ANALYTICAL STUDY OF RAFIDAIN BANK OF IRAQ (2019–2025) - Hadir H Shubbar; Khaled A.M. Abulebda (Scholar Express Journals, 2025)
The banking institution is considered one of the most important financial institutions in the country, playing a vital economic role. The comprehensive electronic banking system also reflects the technological development needed to carry out tasks and provide services to the state in general and to banks in particular. This research discusses the significant role played by the comprehensive electronic system in improving the stability of the banking system's performance through the activation and application of the electronic system in all aspects of banking operations. The study aims to evaluate the efficiency of comprehensive electronic systems in banks to select appropriate measures that would improve banking performance. It addresses the main issue that arises when evaluating the comprehensive electronic system applied by banks in all their transactions and the outcomes of banking performance in various real-world situations. This is done by analyzing the value of inputs and the actual value of outputs. The study also evaluates the impact of the changing competitive environment and the spread of banks implementing comprehensive electronic systems. The research relies on data analysis from Rafidain Bank of Iraq for the period 2019 to 2025, using a value-added methodology to distinguish the interactions between the electronic system and banking performance. The results indicate that the proposed model can help banking sector managers adopt diverse policies across various banking sectors in a competitive environment. It also identifies effective electronic system groupings, allowing for the identification of current reserves, potential management tools, and decisions to improve underperforming systems. Furthermore, the advanced approach to the comprehensive electronic system aims to enhance macro-level bank management and improve banking system efficiency
Keywords: Comprehensive electronic system; banking system performance